STRUCTURAL GEOLOGICAL CONTROL ON THE APPEARANCE OF GEOTHERMAL AREA MANIFESTATION IN GEDONGSONGO, BANDUNGAN, SEMARANG, CENTRAL JAVA BASED ON ANALYSIS OF FAULT FRACTURE DENSITY - Rinjani, Amin (Bulletin of Scientific Contribution, 2024)
Gedong Songo, Ungaran, is a geothermal complex from the part of the Ungaran volcano system which located in the North of the Serayu Mountains as the result of back-arc magmatism during the quaternary period. The presence of surface geothermal manifestations indicates the existence of an active geothermal system in this area. Surface manifestations in Gedong Songo area includes hot springs, fumaroles, steaming ground, and altered rocks. This study uses a lineament analysis on imagery DEM supported by geomagnetic data and geological mapping. The lineament in this area is identified from DEM. Based on geological field observations and mapping, and also manifestations in Gedong Songo  area are controlled by northeast-southwest right strike slip faults structures, and the presence of structures is reinforced by geomagnetic anomalies that indicate areas affected by heat experiencing demagnetization.